1975
DOI: 10.1007/bf00916026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a teacher's presence on the classroom behavior of conduct-problem children

Abstract: Six institutionalized conduct-problem children performed in a classroom under three reinforcement conditions: (1) noncontingent reinforcement: (2) reinforcement for being on task and (3) reinforcement for the accuracy and rate fo their academic behavior. Within each of these conditions, the teacher was either present throughout the class session or absent for a portion of the session. In the teacher's absence, on-task behavior was markedly reduced and disruption was markedly increased, regardless of the reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…However, of particular interest is the finding that the children were less disruptive and tended to remain on task more in the teacher's absence when academic behavior was being reinforced. This is consistent with an earlier study, in which it also was found that the extent to which the children became disruptive in a teacher's absence was reduced when reinforcement was contingent on the accuracy and rate of their behavior, rather than being delivered noncontingently or for simply being on task (Marholin et al, 1975).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, of particular interest is the finding that the children were less disruptive and tended to remain on task more in the teacher's absence when academic behavior was being reinforced. This is consistent with an earlier study, in which it also was found that the extent to which the children became disruptive in a teacher's absence was reduced when reinforcement was contingent on the accuracy and rate of their behavior, rather than being delivered noncontingently or for simply being on task (Marholin et al, 1975).…”
Section: Discussionsupporting
confidence: 92%
“…The increases in task orientation and decreases in disruptive behavior when academic achievement alone was being reinforced are similar to the findings by Ayllon and Roberts (1974), Kirby and Shields (1972), Marholin et al (1975), and Winett and Roach (1972). However, of particular interest is the finding that the children were less disruptive and tended to remain on task more in the teacher's absence when academic behavior was being reinforced.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations